Papillary stenosis of the submandibular gland caused by dental prostheses - Schapher, Mirco; Goncalves, Miguel; Mantsopoulos, Konstantinos; Iro, Heinrich; Koch, Michael (Oral Surgery, Oral Medicine, Oral Pathology and Oral Radiology, 2020)
Objectives: The aim of this study was to assess diagnosis and treatment of submandibular duct stenosis caused by dental prostheses. Study Design: This retrospective study included 9 patients with papillary stenosis caused by physical irritation of the Wharton duct ostium by a mandibular dental prosthesis. Diagnostics included physical examination, as well as transcutaneous and transoral ultrasound examinations. Treatment consisted of duct incision, papillotomy, and subsequent sialendoscopy. After surgery, patients were advised to have the dental prosthesis altered by the dentist and to have regular gland massage. Follow-up data were obtained via telephone interviews. The most important outcome parameter was a symptom-free state. Results: In all 9 patients, the insertion of the sialendoscope was initially impossible because of the stenosis. After duct incision, sialendoscopy ruled out other obstructive causes and inflammatory states, leaving the dental prosthesis as the only underlying cause of the obstruction. Seven of the 9 treated patients were interviewed after a follow-up period of 28.1 (± 25.4) months. The procedures had resulted in all patients being symptom-free, without any reported complications. Conclusions: Mandibular prostheses can cause stenosis of the papillary region with subsequent submandibular duct obstruction. Surgical therapy is easy to perform and results in excellent long-term outcomes.
CRIS-Team Scopus Importer:2020-03-06